Direct manipulation is better than passive viewing for learning anatomy in a three-dimensional virtual reality environment. (March 2017) - Jang, Susan; Vitale, Jonathan M.; Jyung, Robert W.; Black, John B.
Abstract: With the advancement of virtual reality (VR) technologies, medical students may now study complex anatomical structures in three-dimensional (3-D) virtual environments, without relying solely upon high cost, unsustainable cadavers or animal models. When coupled with a haptic input device, these systems support direct manipulation and exploration of the anatomical structures. Yet, prior studies provide inconclusive support for direct manipulation beyond passive viewing in virtual environments. In some cases, exposure to an "optimal view" appears to be the main source of learning gains, regardless of participants' control of the system. In other cases, direct manipulation provides benefits beyond passive viewing. To address this issue, we compared medical students who either directly manipulated a virtual anatomical structure (inner ear) or passively viewed an interaction in a stereoscopic, 3-D environment. To ensure equal exposure to optimal views we utilized a yoked-pair design, such that for each participant who manipulated the structure a single matched participant viewed a recording of this interaction. Results indicate that participants in the manipulation group were more likely to successful generate (i.e., draw) the observed structures at posttest than the viewing group. Moreover, manipulation benefited students with low spatial ability more than students with high spatial ability. These results suggest that direct manipulation of the virtual environment facilitated embodiment of the anatomical structure and helped participants maintain a clear frame of reference while interacting, which particularly supported participants with low spatial ability. Highlights: Virtual reality facilitates exploration of complex anatomy without costly cadavers. Our VR program allows participants to directly manipulate 3-D structures. There are mixed prior results comparing direct manipulation to passive viewing. We show clear advantages for direct manipulation beyond passive viewing. Our results are congruent with an embodied perspective of learning.